Effect of Adding Purslane Flour (Pertulaca oleracea) on feed on the amount of Moulting, Growth and Survival Rate of Vannamei Shrimp (Litopenaeus vannamei) (Jurnal Online Mahasiswa (JOM) Bidang Perikanan dan Ilmu Kelautan, 2019)
ABSTRACTThis research was conducted on September 17 to October 22, 2018 at the Laboratory of Aquaculture Technology, Department of Aquaculture, Faculty of Fisheries and Marine, University of Riau. The chemical analysis of pellets was carried out at the Agricultural Product Technology Laboratory, Faculty of Agriculture, University of Riau. The aim of the study was to determine the effect of adding purslane flour to feed on the amount of moulting, growth and survival of vannamei shrimp. The research method was using an experimental method Complete Random Design (CRD) with 1 factor consisting of 5 treatment levels and three replications. The treatment level used is the dose of purslane 0 g / kg (Control), 10 g / kg, 20 g / kg, 30 g / kg, and 40 g / kg. For the best 35 days of maintenance on the administration of 40 g / kg of purslane flour with the number of moulting shrimp as many as 83 tails, absolute weight growth of 1.08 grams, specific growth rate of 0.08% and survival of 98%. And water quality during the study was 29-30 ºC, pH 6, dissolved oxygen (DO) 3.56-4.2 ppm, salinity 15-18 ppt and ammonia 0.001-0.093 mg/L.Key Word :Litopenaeus vannamei, purslane flour, moulting.